Erratum to: Interrelationships of climate adaptation and organizational learning: Development of a measurement model (Journal of Pedagogical Research, 8(1), 223-243) - Fischer, Sophie; Göhlich, Michael; Schmitt, Jan (Journal of Pedagogical Research, 2024)
Climate adaptation and learning support organizations in coping with the current and projected impacts of climate change by identifying challenges as opportunities, ensuring business continuity and increasing their economic efficiency. In addition to material resources, climate adaptation requires knowledge, technical know-how and the ability to learn. Our article examines the relationship between climate adaptation and organizational learning, as the consideration of climate adaptation in the long term and with regard to organizational learning or reorientation is still very little represented in research. Therefore, a quantitative study is conducted in order to determine whether companies already have climate-related structures conducive to learning, whether they take responsibility for the learning object (climate change), and which elements limit the learning process. The survey of 288 companies and craft businesses in a German industrial region shows that intangible resources such as a sense of responsibility, a positive attitude among managers and shared values have a significant influence on how companies deal with climate change. Managers are key players in setting corporate goals, developing strategies and monitoring functional processes. The study shows that the number of climate-related measures taken is increasing due to higher resource capacities. As we draw conclusions about the changing learning requirements, conditions and media in the face of climate change, the results can provide relevant suggestions for researchers and practitioners to understand climate adaptation as a valuable and strategic challenge and to improve the resilience of the organization itself.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Climate adaptation; Corporate social responsibility; Organization education; Organizational development; Organizational learning